Majlis Dekan-dekan Bahasa Universiti Awam (MaLDeC) and OMNiA Academy explore potential collaboration for educational advancement - Umi Kalsom, Masrom (UMPSA, 2024)
PUTRAJAYA, 22 April 2024 - Key stakeholders from Majlis Dekan-dekan Bahasa Universiti Awam (MaLDeC) and OMNiA Academy Media Prima Sdn. Bhd. convened at the Ministry of Higher Education in Putrajaya.